The Influence of Service Quality and Employee Performance of Pdam Tirta Batang Hari on Customer Satisfaction in The Provision of Clean Water - Satya, Satya Wahyudi; Neng, Neng Setiawati; Boy, Boy Marsukun S (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2023)
Introduction/Main Objectives: The purpose of this research to determinate the effect of service quality and employee performance in the provision of clean water and its effect on customer satisfaction at PDAM Tirta Batang Hari. Background Problems: Customer satisfaction is something that is very important for an economic entity, therefore analyzing service quality and employee service performance on customer satisfaction at Tirta Batanghari Regional Drinking Water Company is very necessary to do. Research Methods: The analysis used in this research is validity test, reliability coefficient of determination, T test, F test. This test aims to find out how much influence there is between variables, which are then analyzed using multiple linear regression with the help of the Statistical Product and Service Solution (SPSS) version. 25.0. Finding/Results: The results of this study are Y = 0.362 + 0.552 X1 + 0.260 X2. This shows that service quality and employee performance have a positive and significant impact on customer satisfaction. Conclusion: The result of the value determination coefficient test obtained is 87.8% meaning that customer satisfaction (Y) at PDAM Tirta Batang Hari is influenced by service quality (X1) and employee performance (X2).